„Kimegyek a doberdói harctérre”: A magyar népdal és az első világháború - Arany, János (Studia Litteraria, 2015)
Folk music – just like any other work of art – bears the historical imprint of the age when it was born. World War military poetry is the last manifestation of the song creating imagination of Hungarian folk culture. Due to cultural history, we have a particularly colourful and nuanced image of the effects of the “Great War” on Hungarian folk music. It is a unique coincidence – both of historical and academic importance – that the significance of folk music and its research was recognized by the whole continent just a decade before the outbreak of the war, that there were two outstanding researchers of folk music in Hungary, and that these two researchers were both excellent composers. Due to the work of Kodály and Bartók, the collection of folk music, which formerly happened in the small villages of the country, spread to military communities, covering the songs that were born during the war. This way, the study of folk music made it possible for scholars to observe the effect of historical events on folk culture through living examples.